FUNGSI BADAN KEPEGAWAIAN, PENDIDIKAN, DAN PELATIHAN KABUPATEN SUKOHARJO DALAM REKRUITMEN CPNS DITINJAU DARI PRINSIP AKUNTABILITAS DAN TRANSPARANSI - Paramita Putri Dewayani (JI@P, 2021)
The research purpose was described the function of BKPP of SukoharjoRegency in civil servant recruitment viewed from the principles of accountabilityand transparency. The research used descriptive qualitative method. Datacollection techniques were used interviews, observation, and documentation. Thedata analysis technique was used Miles and Huberman’s intractive model. Validitydata testing was used triangulation techniques. The evaluation of BKPP ofSukoharjo Regency function in the implementation of CPNS recruitment is viewedfrom the principles of accountability and transparency conveyed by Sedarmayanti(2013). The results of the study indicated that 1 ) Function of BKPP Sukoharjoregency in civil servant recruitment in terms of the accountability principle appearsfrom the implementation of civil servant recruitment carried out in accordance withthe legislation in force as well as the recruitment of civil servant accountable to thepublic and made a report to the parties concerned. 2 ) Functions of the BKPP ofSukoharjo Regency in terms of the transparency principle, the recruitment of CPNSis to carry out the recruitment of CPNS openly step by step. The announcement,application and filtering system is implemented transparently through theapplication of information technology so that the public can access it easily. Basedon the research results, it can be concluded that the BKPP Sukoharjo Regency hasimplemented the principles of accountability and transparency in carrying out itsfunctions in the implementation of CPNS recruitment in Sukoharjo Regency.